Efficacy of Pre-Treatment with Remimazolam on Prevention of Propofol-Induced Injection Pain in Patients Undergoing Abortion or Curettage: A Prospective, Double-Blinded, Randomized and Placebo-Controlled Clinical Trial - Guan X; Jiao Z; Gong X; Cao H; Liu S; Lan H; Huang X; Tan Y; Xu B; Lin C (Dove Medical Press, 2021)
Xuehai Guan,1,* Ziyin Jiao,1,* Xiaofang Gong,1 Huiyu Cao,1 Susu Liu,1 Hongmeng Lan,1 Xiaofang Huang,1 Yanmeng Tan,1 Bing Xu,2 Chengxin Lin1 1Department of Anesthesiology, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of China; 2Department of Rehabilitation, The People`s Hospital of Guangxi Zhuang Autonomous Region, Nanning, Guangxi, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuehai Guan; Chengxin LinDepartment of Anesthesiology, The First Affiliated Hospital of Guangxi Medical University, 6 Shuangyong Road, Nanning, Guangxi, 530021, People's Republic of ChinaTel/Fax +86-771-5356250Email guan_xh@aliyun.com; lin.chx@163.comBackground: Propofol-induced injection pain (PIP) is a well-known problem in general anesthesia. We hypothesized that pre-treatment with remimazolam prevents PIP in patients undergoing abortion or curettage.Materials and Methods: In this prospective, single-center, double-blinded, randomized, placebo-controlled clinical trial, adult patients aged 18 to 60 undergoing abortion or curettage were randomly assigned to three groups. Group Lido received system lidocaine (a bolus of 0.5 mg kg− 1, iv). Group Remi received remimazolam (a bolus of 0.1 mg kg− 1, iv). Group NS received identical volumes of 0.9% normal saline. Sixty seconds after the injection of lidocaine, remimazolam or saline, patients were injected with propofol at a rate of 12 mL/min until the loss of consciousness. The primary outcome was the incidence of PIP at the time of induction using 4-point scale. Secondary outcomes included propofol-induced injection pain, vital signs, the characteristics of anesthesia and surgery, and adverse events.Results: The incidence of patients with PIP was higher in group NS than that in group Lido and group Remi (75.7, 44.3, and 42.9%, respectively, p < 0.001). The percentages of patients with moderate PIP were higher in group NS than that in group Lido and group Remi (20.0, 2.9, and 1.4%, respectively, p < 0.001). Moreover, the consumption of propofol and the incidence of adverse event (hypoxemia and chin lifting) in group Remi were lower than that in group NS and Lido, and less patients got physical movement and cough in group Remi. The recovery time in group NS was longer than that in group Lido and Remi.Conclusion: Our findings indicate that pre-treatment with remimazolam reduced the incidence and intensity of PIP in abortion or curettage patients, equivalent to that of lidocaine without severe adverse effects.Trial Registration: Chinese Clinical Trial Registry (identifier: ChiCTR2100041805).Keywords: lidocaine, remimazolam, propofol injection pain, abortion, curettage